Luchas sociales, justicia contextual y dignidad de los pueblos - Salas, Ricardo (Ariadna Ediciones, 2020)
Set of works of renowned Latin American intellectuals about the current political and social situation in our region, especially after the events of Ecuador, Brazil and Chile